COMPONENTS OF EDUCATIONAL SUPERVISION IN ISLAMIC EDUCATION: ACADEMIC, SPIRITUAL, AND MANAGERIAL INTEGRATION FOR QUALITY IMPROVEMENT - Masruri; Dwika Putra; Almahfuz; Linda (Journal International Inspire Education Technology, 2026)
Supervision of education in Islamic education is an important issue because improving the quality of institutions is not enough to be achieved through strengthening learning alone, but requires integration between academic coaching, internalization of spiritual values, and the effectiveness of institutional governance. This article aims to analyze the components of educational supervision in Islamic education and formulate the integration of academic, spiritual, and managerial aspects as a quality improvement strategy. This study uses a qualitative approach based on literature studies with thematic analysis techniques and narrative synthesis on various relevant literature regarding Islamic education supervision, academic supervision, Qur’anic values in educator development, and educational quality management. The results of the study show that academic supervision plays a role in improving the quality of learning and teacher professionalism, spiritual supervision strengthens the mandate, example, and moral integrity of educators, while managerial supervision ensures program regularity, institutional coordination, and sustainability of quality evaluation. This study also confirms that improving the quality of Islamic education will be more effective if the three components are integrated in one planned, multidimensional, and sustainable coaching system. Thus, Islamic education supervision must be positioned as a strategic instrument to build a quality of education that is holistic, contextual, and relevant to contemporary institutional demands.